A casework study comparing success rates and expectations of detecting male DNA using two different Y-STR multiplexes on vaginal swabs in sexual assault investigations where no semen has been detected. (November 2018) - Owers, R.; McDonald, A.; Montgomerie, H; Morse, C
Highlights: Comparison of Y-STR profiling results analysed using Yfiler ® with those analysed using Powerplex ® Y23, using data from 250 criminal cases. Demonstrates the value of using more recently developed Y-STR multiplexes compared with older kits. Male DNA can be detected using Y-STR analysis up to 48h after the alleged incident in digital penetration cases and up to 6 days in penile penetration cases. Male DNA can be detected on high vaginal swabs in cases of alleged digital penetration. Sensitivity of Y-STR analysis routinely detects male DNA even when quantification does not identify male DNA in the sample. Abstract: Sexual assault cases where there is an allegation of digital or penile penetration but no semen is detected on the vaginal swabs have historically been difficult to investigate due to the high background levels of female DNA present. Previous studies have shown the value of Y-STR analysis in such cases. This study aims to provide: success rate data from vaginal swabs received in 250 cases of alleged penetration where no semen has been detected, comparing results obtained from an older Y-STR multiplex (Yfiler ® ) with those obtained from a more recently developed Y-STR multiplex (Powerplex ® Y23). data on the expectation of detecting male DNA for a range of time since intercourse in digital penetration only cases and by providing maximum time periods for the detection of male DNA in digital and/or penile penetration cases within this study. data on which sets of vaginal swabs should be considered for Y-STR analysis in cases of alleged digital penetration only. 17% of the cases in this study generated Y-STR profiles suitable for subjective or statistical evaluation following analysis with Yfiler ® compared with 34% of the cases analysed with Powerplex ® Y23, demonstrating the value of using more recently developed Y-STR multiplexes compared with older kits.